Kaitan psychological well being pada work engagement karyawan PT Semen Indonesia Distributor - Ilmiawan, Achmad Rouf; Sukiatni, Sarwendah; Kusumandari, Rahma (JIWA: Jurnal Psikologi Indonesia, 2023)
Employees are the most valuable resource in an organization and providing them with a stable long-term career is a win-win situation for both the organization and the employee. Therefore, companies must have employees who have good work engagement. Employees with good work engagement will bring enthusiasm, dedication and appreciation to work. This research was conducted with the aim of knowing the relationship between psychological well-being and work engagement among PT Semen Indonesia Distributor employees. This study uses a correlational quantitative method. The population in this study were 300 employees of PT Semen Indonesia Distributor. Sampling in this study using accidental sampling technique. The participants used in this study were 173 employees of PT Semen Indonesia Distributor. The data collection method uses a Likert scale. The measuring instrument used is a modified scale of work engagement scale and psychological well being scale. Hypothesis testing in this study used Spearman's rho correlation with the help of SPSS (Statistical Product and Service Solution) for window version 25. The results of data analysis showed that the rho value = 0.207 with a significance of p = 0.015 (p <0.05) so that there is a positive relationship between psychological well being with work engagement on employees of PT Semen Indonesia Distributor. Karyawan adalah sumber daya yang paling bernilai dalam organisasi dan memberinya karir jangka panjang yang stabil adalah suatu situasi yang saling menguntungkan baik bagi organisasi maupun bagi karyawan. Oleh sebab itu perusahaan harus memiliki karyawan yang memiliki work engagement yang baik. Karyawan dengan work engagement yang baik akan memunculkan semangat, dedikasi dan penghayatan dalam bekerja. Penelitian ini dilaksanakan dengan tujuan untuk mengetahui hubungan psychological well being dengan work engagement pada karyawan PT Semen Indonesia Distributor. Penelitian ini menggunakan metode kuantitatif korelasional. Populasi pada penelitian ini sebanyak 300 karyawan PT Semen Indonesia Distributor. Pengambilan sampel pada penelitian ini menggunakan teknik Accindental sampling. Partisipan yang digunakan dalam penelitian ini sebanyak 173 karyawan PT Semen Indonesia Distributor. Metode pengumpulan data menggunakan skala likert. Alat ukur yang digunakan adalah skala modifikasi skala work engagement dan skala psychological well being. Pengujian hipotesis pada penelitian ini menggunakan korelasi Spearman’s rho dengan bantuan SPSS (Statistical Product and Service Solution) for window versi 25. Hasil analisis data menunjukkan nilai rho sebesar = 0,207 dengan signifikansi sebesar p = 0,015 (p<0.05) sehingga ada hubungan positif antara psychological well being dengan work engagement pada karyawan PT Semen Indonesia Distributor .